Una Apreciación de las Contribuciones Vitalicias de Vic Sidel a la Paz y la Justicia Social / An Appreciation of Vic Sidel’s Lifelong Contributions to Peace and Social Justice - Gould, Robert M. (Medicina Social / Social Medicine, 2013)
Este artículo presenta una apreciación personal de las contribuciones vitalicias de Victor W. Sidel, MD, a la paz y la justicia social, ejemplificadas por su trabajo en Médicos por la Responsabilidad Social y en la Asociación Americana de Salud Pública. Abstract: This article presents a personal appreciation of the lifetime contributions of Victor W. Sidel, MD, to peace and social justice, exemplified by his work in Physicians for Social Responsibility and the American Public Health Association.